Case report: Characteristics and nature of primary cardiac synovial sarcoma - Kawasaki, Tomonori; Nakajima, Tomomi; Torigoe, Tomoaki; Onohara, Kojiro; Ishii, Kentaro; Kanno, Satoshi; Muramatsu, Chisako; Tatsuno, Rikito; Jubashi, Takahiro; Ichikawa, Jiro (Frontiers in Oncology, 2024)
Primary malignant cardiac tumors rarely occur, and cardiac synovial sarcoma (SS) is especially rare among such tumors. Herein, we present the case of a 35-year-old female with primary cardiac SS treated with surgery, chemotherapy, and radiotherapy. She presented with chest symptoms and underwent imaging examinations. A cardiac tumor was suspected, and an open biopsy was performed. The pathological findings suggested cardiac SS. Next, we performed a resection, and the tumors persisted at a macroscopic level. Immunohistochemistry was negative for SS18-SSX and positive for the SSX C-terminus and cytokeratin CAM5.2, a reduction of SMARCB1/INI1 was observed, and fluorescence in situ hybridization showed positive SS18 split staining. Owing to the FNCLCC grade 3 tumor and R2 margins, adjuvant chemotherapy with ifosfamide, doxorubicin, and radiotherapy was initiated, and the patient was diagnosed with cardiac SS. The differences in patients with cardiac SS compared with general SS include male predominace, larger tumor size, and poorer prognosis. Pathological findings of immunohistochemistry and fluorescence in situ hybridization were found to be more reliable than imaging findings for a correct diagnosis. Additionally, because incomplete resection is frequently performed, adjuvant therapy, including chemotherapy and radiation therapy, may be performed. The findings indicate that multiple therapies, including surgery, chemotherapy, and radiotherapy, are essential treatment strategies for improving the prognosis of patients with cardiac SS.